Reversible inhibition of sperm under guidance as an intratubular and reversible contraception in female rats: An experimental study - Abdul Salam Ansari; Kiran Sevliya; Ayesha Badar; Nirmal Kumar Lohiya (Shahid Sadoughi University of Medical Sciences, 2021)
Background: Reversible inhibition of sperm under guidance ("RISUGⓇ ") is a promising intravasal male contraceptive. Objective: An exploratory study was conducted with a concept of non-invasive, transcervical, single-intervention and reversible contraception using RISUGⓇ in females. Materials and Methods: In this experimental study, 60 adult Wistar albino female rats weighing 150-155 g, 3-4 months old were divided into four groups: group I: sham-operated control; group II: tubal occlusion with RISUG for 90 days; group III: tubal occlusion with RISUGⓇ for 90 days and reversal with dimethyl sulphoxide and group IV: tubal occlusion with RISUGⓇ for 90 days and reversal with 5% NaHCO 3 . Animals were subjected to bilateral fallopian tube occlusion with RISUGⓇ and reversal with DMSO and NaHCO 3 . The estrous cycle, fertility and histology of fallopian tube were evaluated. Results: Group I showed 100% fertility during all mating schedules. Animals of experimental groups indicated positive mating, but 0% fertility was evident following 30, 60, and 90 days of tubal occlusion. However, after reversal, fertility steadily increased to normalcy in groups III (50% at 45 days, 80% at 105 days, 100% at 150 and 195 days) and IV (70% at 45 and 105 days, 100% at 150 and 195 days) animals. Group II illustrated disorganized inner cell linings and eosinated RISUGⓇ implant-filled lumen. Reversal groups (III and IV) revealed complete restoration of cellular histo-architecture. Regular estrous cycle was noticed in all experimental groups. Conclusion: RISUGⓇ is suitable for single intervention, intratubular, reversible contraception in female rats.Key words: Contraception, Fallopian tube, Tubal occlusion, RISUGⓇ , Reversible.